Sca-1 expression depicts pro-inflammatory murine neutrophils under steady-state and pathological conditions - Milind Nahiyera; Supriya Sinha; Priyanka Dhankani; Apurwa Singhal; Abhinav Singh; Rakesh Kumar Sharma; Ambalika Gond; Prayrna Atter; Kanchan Gupta; Kalyan Mitra; Amit Lahiri; Kumarvelu Jagavelu; et al. (Cell Reports)
Summary: Neutrophils play a critical role in various pathophysiological conditions. However, their therapeutic targeting has been challenging due to the associated risk of infections. Therefore, identifying disease-associated neutrophil populations is essential for targeted strategies. This study identifies a distinct neutrophil subpopulation, CD11b+Ly6G+Sca-1+ neutrophils expressing stem cell antigen-1 (Sca-1). Sca-1pos neutrophils, enriched in the liver, are mature, long lived, and proinflammatory. They display enhanced effector functions, including superoxide production, degranulation, NETosis, and T cell proliferation. Sca-1 is not merely a marker but actively contributes to these functions. Intriguingly, inflammatory and metabolic cues drive the emergence of Sca-1pos neutrophils from conventional neutrophils and progenitors. Models of acute and chronic inflammatory conditions such as peritonitis and non-alcoholic steatohepatitis demonstrate increased Sca-1pos neutrophils. Pharmacological interventions reduce their enhanced functional activity and associated inflammatory outcomes. Collectively, this work reveals a distinct inflammatory neutrophil subpopulation and provides a potential avenue for selectively targeting neutrophil subpopulations in inflammatory diseases.